Mavrilimumab in patients with severe COVID-19 pneumonia and systemic hyperinflammation (MASH-COVID): an investigator initiated, multicentre, double-blind, randomised, placebo-controlled trial. (June 2021) - Cremer, Paul C; Abbate, Antonio; Hudock, Kristin; McWilliams, Carla; Mehta, Jinesh; Chang, Steven Y; Sheng, Calvin C; Van Tassell, Benjamin; Bonaventura, Aldo; Vecchié, Alessandra; Carey, Brenna; Wang, Qiuqing; et al.
Summary: Background: In patients with COVID-19, granulocyte-macrophage colony stimulating factor (GM-CSF) might be a mediator of the hyperactive inflammatory response associated with respiratory failure and death. We aimed to evaluate whether mavrilimumab, a monoclonal antibody to the GM-CSF receptor, would improve outcomes in patients with COVID-19 pneumonia and systemic hyperinflammation. Methods: This investigator-initiated, multicentre, double-blind, randomised trial was done at seven hospitals in the USA. Inclusion required hospitalisation, COVID-19 pneumonia, hypoxaemia, and a C-reactive protein concentration of more than 5 mg/dL. Patients were excluded if they required mechanical ventilation. Patients were randomly assigned (1:1) centrally, with stratification by hospital site, to receive mavrilimumab 6 mg/kg as a single intravenous infusion, or placebo. Participants and all clinical and research personnel were masked to treatment assignment. The primary endpoint was the proportion of patients alive and off supplemental oxygen therapy at day 14. The primary outcome and safety were analysed in the intention-to-treat population. This trial is registered at ClinicalTrials.gov, NCT04399980, NCT04463004, and NCT04492514 . Findings: Between May 28 and Sept 15, 2020, 40 patients were enrolled and randomly assigned to mavrilimumab (n=21) or placebo (n=19). A trial of 60 patients was planned, but given slow enrolment, the study was stopped early to inform the natural history and potential treatment effect. At day 14, 12 (57%) patients in the mavrilimumab group were alive and off supplemental oxygen therapy compared with nine (47%) patients in the placebo group (odds ratio 1·48 [95% CI 0·43–5·16]; p=0·76). There were no treatment-related deaths, and adverse events were similar between groups. Interpretation: There was no significant difference in the proportion of patients alive and off oxygen therapy at day 14, although benefit or harm of mavrilimumab therapy in this patient population remains possible given the wide confidence intervals, and larger trials should be completed. Funding: Kiniksa Pharmaceuticals.